Integrasi Permainan Olahraga Tradisional dalam Pembelajaran Sastra Inggris: Pendekatan Kolaboratif untuk Meningkatkan Literasi dan Aktivitas Fisik Siswa - Uci Dwi Cahya; Muhammad Syahtiri; Edi Safwan; M. Alif Hamzah (WISE Pendidikan Indonesia, 2026)
Traditional games as part of local culture are increasingly being abandoned in educational activities. This study was conducted to examine the impact of integrating traditional sports games into English Literature instruction on students’ literacy competence, level of physical engagement, learning motivation, and appreciation of cultural values. A quantitative research design was adopted through a quasi-experimental approach employing a Pretest–Posttest Control Group Design. The participants were divided into two groups, namely an experimental group and a control group, with 25 students in each class. Data collection techniques included pretests and posttests, observations of physical activities, Likert-scale questionnaires, and supporting documentation. The collected data were processed using descriptive statistical analysis and independent t-tests. The results demonstrated a substantial increase in the experimental group’s mean score, rising from 61.4 on the pretest to 84.2 on the posttest, whereas the control group showed a more moderate improvement from 60.8 to 72.1. Statistical testing produced a significance value of 0.003 (p < 0.05), confirming that the intervention had a significant positive effect on students’ literacy achievement. Furthermore, the experimental group attained an average physical activity level of 86%, categorized as active, compared to 62% in the control group. Findings from the questionnaire indicated a high level of learning motivation, with a mean score of 4.4 out of 5, and 88% of participants reporting that the instructional activities were more engaging and enjoyable. Furthermore, 84% of students became more familiar with traditional games, and 81% expressed greater pride in their local culture. Therefore, integrating traditional sports games into English Literature learning proved effective in improving academic achievement, physical activity, learning motivation, and students’ cultural awareness